The role of the maternal and fetal inflammatory response in retinopathy of prematurity. (24th May 2018) - Lynch, Anne M.; Berning, Amber A.; Thevarajah, Tamara S.; Wagner, Brandie D.; Post, Miriam D.; McCourt, Emily A.; Cathcart, Jennifer N.; Hodges, Jennifer K.; Mandava, Naresh; Gibbs, Ronald S.; Palestine, Alan G.
Abstract : Problem: There is a paucity of research on the contribution of placental inflammation to severe retinopathy of prematurity (ROP). Method of Study: A retrospective cohort study (n = 1217) was conducted of infants screened for ROP (2006‐2016). The outcomes of the study were severe ROP (type 1 or type 2 ROP) and low grade ROP. We categorized the placental pathology as the presence of (i) maternal plus fetal inflammatory response, (ii) maternal inflammatory response only, (iii) fetal inflammatory response only and, (iv) no evidence of a maternal or fetal inflammatory response. The data were analyzed using univariate and multivariate logistic regression analyses ( P  < .05). Results: In this cohort, the number of infants with the maternal plus fetal inflammatory response, the maternal inflammatory response only, the fetal inflammatory response only, and no maternal or fetal inflammatory response was 305 (25%), 82 (7%), 8 (1%), and 822 (67%), respectively. Adjusted for covariates, the maternal plus fetal inflammatory response was a significant risk factor for severe ROP (AOR = 2.6, 95% CI 1.1‐5.9, P  = .03). None of the categories of placental inflammation were significantly associated with low grade ROP. Conclusion: Placental pathology distinguished by the maternal plus fetal inflammatory response was a significant risk factor for severe ROP. Our study supports a link between intrauterine inflammatory events and the subsequent development of severe ROP.